2012
DOI: 10.1155/2012/964093
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Giant Splenic Artery Aneurysm

Abstract: Introduction. Visceral artery aneurysms are uncommon. Among them, splenic artery is the most common (46–60%). Most splenic artery aneurysms are asymptomatic and diagnosed incidentally, but its rupture, potentially fatal, occurs in up to 8% of cases. Presentation of Case. A female patient, 64 years old, diagnosed with a giant aneurysm of the splenic artery (approximately 6.5 cm in diameter) was successfully submitted to endovascular treatment by stent graft implantation. Discussion. Symptomatic aneurysms and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…SAAs are the most frequent splanchnic artery aneurysms, constituting 50–70% of these aneurysms. 7 , 9 , 15 In addition, SAAs are the third most frequent intraabdominal aneurysms, following abdominal aorta and iliac artery aneurysms. 13 , 17 SAAs were first defined by Beaussier in 1770 in a cadaver study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAAs are the most frequent splanchnic artery aneurysms, constituting 50–70% of these aneurysms. 7 , 9 , 15 In addition, SAAs are the third most frequent intraabdominal aneurysms, following abdominal aorta and iliac artery aneurysms. 13 , 17 SAAs were first defined by Beaussier in 1770 in a cadaver study.…”
Section: Discussionmentioning
confidence: 99%
“…13 , 17 SAAs were first defined by Beaussier in 1770 in a cadaver study. 15 , 17 , 69 Hoegler diagnosed these lesions preoperatively with radiologic interventions in 1920. 69 Although the true incidence of SAA is unclear, various studies of autopsies, angiography findings, and autopsies of individuals ≥60 years revealed rates of 0.01–0.2%, 0.78–0.80%, and 10.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The aneurysm mostly lies at the distal portion of splenic artery and near the splenic hilum and true aneurysm originating from the initial part of splenic artery is extremely rare [6] . The size of an aneurysm is usually 2-5 cm, and few are larger than 10 cm [4,11] . Aneurysms tend to be fusiform, capsular, spherical and even bead-like shape [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Obuchi et al [12] and Wei et al [2] believed that, for aneurysms greater than 5 cm, or with a wide neck, or in the vicinity of hepatic artery or celiac trunk, interventional therapy is very difficult and tend to cause complications. In these cases, traditional open surgery, consisting of aneurysmectomy and vascular reconstruction, are the treatment of choice because they relatively safe and reliable in these cases [4,[18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation